Detection of Enterococcus faecalis in subgingival biofilms of healthy, gingivitis, and chronic periodontitis subjects - Chethana Kunthur Chidambar; Shrinidhi Maji Shankar; Pooja Raghu; Soumya Badravalli Gururaj; Kala Shashi Bushan (Wolters Kluwer Medknow Publications, 2019)
Background: Enterococcus faecalis is a Gram-positive, facultative anaerobic coccus that can survive under harsh conditions. Studies have shown a positive relationship between biofilm formation and gelE gene expression in E. faecalis. The production of gelatinase (MMP 2) has been detected in 50% of E. faecalis isolates from endodontic and periodontal infections, which suggests its role in the pathogenesis of apical and marginal periodontitis. Although E. faecalis is not considered a periodontopathogen, this species has been more frequently detected in subgingival samples with periodontitis than from periodontally healthy subjects, suggesting that the local conditions in periodontitis may favor its colonization. Hence, the aim of the current study was to detect and compare the presence of E. faecalis in subgingival biofilms of healthy, gingivitis, and periodontitis subjects. Materials and Methods: A total of 100 subjects aged between 25 and 55 years, from the Outpatient Department of Periodontics were recruited for the study. All the subjects were screened for gingival and periodontal status using plaque index, gingival index, and clinical attachment loss. They were divided into three groups based on the clinical findings. Group A: 18 healthy individuals (gingival index with score zero) Group B: 34 gingivitis patients (gingival index with score >1) Group C: 48 chronic periodontitis patients (clinical attachment loss >5 mm in >30% of sites). Subgingival plaque samples of all the enrolled subjects were collected using a sterile curette, later poured into a transport medium (Viability Medium Goteborg Agar III) and sent for microbial culturing within 2 h for detection of E. faecalis. Results: E. faecalis was detected in 26.8% of all samples evaluated. There was a significantly higher frequency of E. faecalis in subgingival biofilms of periodontitis group (41.7%), compared to gingivitis (5.9%) and healthy group (0%). Conclusion: Enterococci may contribute to increased collagen and periodontal destruction and may further lead to disease progression in patients with chronic periodontitis.